Synthesis and Biological Evaluation of Novel Ramalin Derivatives as Multi-Target Agents for Alzheimer’s Disease - Tai Kyoung Kim; Ju-Mi Hong; Yongeun Cho; Yeji Jeon; Heewon Cho; Jeongmi Lee; Jaewon Kim; Kyung Hee Kim; Il-Chan Kim; Se Jong Han; Hyuncheol Oh; Dong-Gyu Jo; et al. (Molecules)
Alzheimer’s disease (AD) is a complex neurodegenerative disorder characterized by cognitive decline, oxidative stress, neuroinflammation, amyloid-beta (Aβ) accumulation, and tau protein hyperphosphorylation. In this study, we synthesized novel Ramalin derivatives and evaluated their therapeutic potential against AD, focusing on antioxidant, anti-inflammatory, and neuroprotective activities. RA-2OMe, RA-4OMe, RA-2CF3, and RA-4OCF3 showed strong antioxidant effects, while RA-2OMe exhibited potent NO and NLRP3 inhibition (~20%). RA-NAP, RA-PYD, and RA-2Q showed moderate anti-inflammatory activity. BACE-1 inhibition was significant in RA-3CF3, RA-NAP, and RA-PYD, with IC50 values lower than that of positive control, indicating greater inhibitory potency. RA-NAP and RA-PYD effectively inhibited both Aβ and tau aggregation, highlighting their multi-target potential for AD therapy. These findings indicate that Ramalin derivatives exhibit potential for multi-target activity in AD treatment. However, further studies on their pharmacokinetics, in vivo efficacy, and long-term safety are required to confirm their therapeutic applicability.